PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 57 PEKANBARU - Lidya Hermayanti; Lazim N Lazim N; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The goal of this research is to increase the result of sains at the fifth grade of SDN 57 Pekanbaru with implementation of the model teaching cooperative type student facilitator and explaining. The background of the problems in this research is the result of sains study is still low, it can be seen from the student score of 20 students that did not get KKM (criteria of minimum success) 13 students (65,00%), were as that getting from KKM was only 7 students (35,00%) with the mean score was 63,20. KKM which have been constanted of the school is 70 based on the problems above, so with implementation of the model of teaching cooperative type student facilitator and explaining. On the I syclus was the activity percentage of the first meeting the teacher got 66,67%, on the second meeting the percentage increase till 75,00%. On the II syclus of the first meeting the percentage increase till 91,67%, on the second meeting the percentage increase become 95,83. Student activity got increasing, on the I syclus the student activity percentage got 66,67%, on the second meeting the percentage increase become 79,16%. On the II syclus the percentage of the first meeting increase become 91,67% and on the second meeting the percentage increase become 95,83%. The mean of the success before implementation was 63,2 and increase become 68,2 in the first syclus. Were as the classical success in the I syclus and the II syclus are increased. The implementation of the model of teaching cooperative type student facilitator and explaining. It can be seen from the result of sains study at the fifth grade of SDN 57 PekanbaruKey Words: The result of studing , model cooperative model type student facilitator andexplaining, Natural Science Subject.